A Priority-Based CSMA/CA Mechanism to Support Deadline-Aware Scheduling in Home Automation Applications Using IEEE 802.15.4. (16th May 2013) - Collotta, Mario; Scatà, Gianfranco; Pau, Giovanni
Abstract : The wireless sensor networks (WSNs) are characterized by several small nodes able to perform measurements on one or more parameters and to communicate with each other through several protocols. Most of home automation networks (depending on the specific application) are mainly characterized by periodic traffic flows. In soft real-time contexts, the main problem is represented by the efficient allocation of guaranteed time slots (GTSs) for periodic traffic flows transmission in IEEE 802.15.4 networks. Moreover, it is important to ensure adequate performance for those embedded devices competing for the access to the medium through the carrier sense multiple access/collision avoidance algorithm (CSMA/CA). The main aim of this paper is to show a new approach for network flows scheduling in home automation applications based on IEEE 802.15.4 wireless sensor networks. This work addresses several advantages due to the introduction of rate monotonic (RM) for guaranteed time slots (GTSs) allocation combined with priority-based CSMA/CA for latencies reduction on transmission attempts as clearly demonstrated by obtained results.